Implementation of Restorative Justice for Narcotics Abuse Cases at the Integrated Assessment Institution of Bnn Gorontalo Province - Benny Lefrans Rondonuwu; Darmawati Darmawati; Kingdom Makkulawuzar (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study aims to analyze the implementation of restorative justice in handling narcotics abuse through the Integrated Assessment Team (TAT) at the National Narcotics Agency of Gorontalo Province and identify various obstacles faced in its implementation. The research method used is empirical legal research with legislative, case, and sociological approaches. Data were obtained through interviews, documentation, and literature studies, then analyzed qualitatively descriptively. The results of the study show that the application of restorative justice has been carried out through an integrated assessment mechanism that functions to determine the feasibility of rehabilitation for narcotics abusers based on medical and legal aspects. This approach makes a positive contribution to reducing the overcapacity of correctional institutions and increasing recovery opportunities for narcotics abusers. However, its implementation still faces various obstacles, including limited human resources, facilities and infrastructure, lack of optimal coordination between law enforcement agencies, and the stigma of the community against narcotics abusers. Therefore, optimization efforts are needed through strengthening regulations, improving the quality of human resources, and increasing synergy between institutions to realize more effective and fair law enforcement.